Clinical and genetic characteristics in lymphoma patients with a second solid malignancy - Zhou, Di; Han, Leng; Jin, Chanjuan; Bi, Lintao (Frontiers in Oncology, 2023)
Diagnosis and treatment of multiple primary malignancies are becoming a new challenge in clinical practice worldwide. The present study aimed to characterize the clinical and genetic features of multiple primary malignancies in patients with synchronous or metachronous lymphoma and another solid tumor. We retrospectively analyzed 11 cases with lymphoma and another solid tumor. The germline mutations in plasma cell-free DNA samples and somatic mutations in lymphoma and solid tumor tissue samples were identified using targeted next-generation sequencing. In the 11 lymphoma patients, the most common type of concurrent solid tumor was colon adenocarcinoma (case 3, 5, 9 11) followed by papillary thyroid carcinoma (case 1, 7, 10). Metachronous lymphoma and solid tumor in 6 patients were treated with corresponding standard therapy asynchronously. Chemotherapy for colon adenocarcinoma during the interval of lymphoma chemotherapy led to excellent outcome in two patients. Immediate chemotherapy for lymphoma plus elective surgery for synchronous papillary thyroid carcinoma also yielded good prognosis in two patients with synchronous double primaries. Interestingly, we found that 10 of 11 patients with lymphoma and another solid tumor harbored germline mutations in Fanconi anemia complementation group (FANC) genes, including FANCI, FANCA, FANCG, FANCL, FANCD1, FANCF, FANCJ, and FANCS. In summary, comprehensive study of the clinical and genetic features of patients with multiple primary malignancies may improve diagnosis and treatment in the future. Mutations in FANC genes might be a predisposition to tumorigenesis of lymphoma patients with a second solid malignancy.